Genetic Diversity and Gene Family Expansions in Members of the Genus Entamoeba. (21st January 2019) - Wilson, Ian W; Weedall, Gareth D; Lorenzi, Hernan; Howcroft, Timothy; Hon, Chung-Chau; Deloger, Marc; Guillén, Nancy; Paterson, Steve; Clark, C Graham; Hall, Neil
Abstract: Amoebiasis is the third-most common cause of mortality worldwide from a parasitic disease. Although the primary etiological agent of amoebiasis is the obligate human parasite Entamoeba histolytica, other members of the genus Entamoeba can infect humans and may be pathogenic. Here, we present the first annotated reference genome for Entamoeba moshkovskii, a species that has been associated with human infections, and compare the genomes of E. moshkovskii, E. histolytica, the human commensal Entamoeba dispar, and the nonhuman pathogen Entamoeba invadens . Gene clustering and phylogenetic analyses show differences in expansion and contraction of families of proteins associated with host or bacterial interactions. They intimate the importance to parasitic Entamoeba species of surface-bound proteins involved in adhesion to extracellular membranes, such as the Gal/GalNAc lectin and members of the BspA and Ariel1 families. Furthermore, E. dispar is the only one of the four species to lack a functional copy of the key virulence factor cysteine protease CP-A5, whereas the gene's presence in E. moshkovskii is consistent with the species' potentially pathogenic nature. Entamoeba moshkovskii was found to be more diverse than E. histolytica across all sequence classes. The former is ∼200 times more diverse than latter, with the four E. moshkovskii strains tested having a most recent common ancestor nearly 500 times more ancient than the tested E. histolytica strains. A four-haplotype test indicates that these E. moshkovskii strains are not the same species and should be regarded as a species complex.